Hispidulin Protects C6 Astroglial Cells Against H2O2-Induced Injury by Attenuating Oxidative Stress, Inflammation, and Apoptosis - Ji-Hyun Kim; Qiqi Pang; Bohkyung Kim; Eun Ju Cho (Applied Sciences, 2025)
Oxidative stress occurs when excessive production of reactive oxygen species (ROS) disrupts the redox balance between oxidants and antioxidants. The brain is particularly vulnerable to oxidative stress due to its high metabolic rate. Astrocytes, the key homeostatic cells in the brain, play a crucial role in maintaining physiological function, including the regulation of oxidative stress. In the present study, we investigated whether hispidulin can mitigate oxidative damage by regulating redox imbalance, inflammatory signaling and apoptotic response in hydrogen peroxide (H2O2)-treated C6 astroglial cells. The cells were exposed to hispidulin at various concentrations for 24 h and then challenged with H2O2 for another 24 h. Hispidulin treatment significantly increased the viability in all concentrations and attenuated H2O2-induced increases in ROS production, lactate dehydrogenase release, and nitric oxide levels. Furthermore, it significantly downregulated proinflammatory markers, including tumor necrosis factor α, interleukin-6 (IL-6), and IL-1β. Western blot analysis exhibited that hispidulin significantly increased the antioxidant defense system-related proteins such as nuclear factor erythroid 2-related factor 2, glutathione peroxidase 1, and superoxide dismutase. In addition, hispidulin decreased the pro-apoptotic Bax and cytochrome C, while increasing the levels of anti-apoptotic Bcl-2. In conclusion, hispidulin showed a protective effect against H2O2-induced injury in C6 astroglial cells by suppressing oxidative stress, inflammation, and apoptosis.